2014
DOI: 10.1063/1.4900856
|View full text |Cite
|
Sign up to set email alerts
|

The HCO+–H2 van der Waals interaction: Potential energy and scattering

Abstract: We compute the rigid-body, four-dimensional interaction potential between HCO(+) and H2. The ab initio energies are obtained at the coupled-cluster single double triple level of theory, corrected for Basis Set Superposition Errors. The ab initio points are fit onto the spherical basis relevant for quantum scattering. We present elastic and rotationally inelastic coupled channels scattering between low lying rotational levels of HCO(+) and para-/ortho-H2. Results are compared with similar earlier computations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 43 publications
7
23
0
Order By: Relevance
“…The results of the plane‐wave calculations (with a MT basis set) are in a reasonable agreement in both E int and ▵E ZPE from the Gaussian‐orbital calculations. However, both DFAs overbind the complex by up to 10 kJ/mol compared to our CP–MP2/CBS+δ(T) results at the respective minima, and by up to 13 kJ/mol compared to the previous correlated wavefunction theory results . For comparison, the E int at the optimised geometry obtained with a state‐of‐the‐art single‐hybrid DFA (ωB97M‐V) is within 2.5 kJ/mol of the CP‐MP2/CBS+δ(T) result.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The results of the plane‐wave calculations (with a MT basis set) are in a reasonable agreement in both E int and ▵E ZPE from the Gaussian‐orbital calculations. However, both DFAs overbind the complex by up to 10 kJ/mol compared to our CP–MP2/CBS+δ(T) results at the respective minima, and by up to 13 kJ/mol compared to the previous correlated wavefunction theory results . For comparison, the E int at the optimised geometry obtained with a state‐of‐the‐art single‐hybrid DFA (ωB97M‐V) is within 2.5 kJ/mol of the CP‐MP2/CBS+δ(T) result.…”
Section: Resultssupporting
confidence: 65%
“…The interaction energy obtained with the latter is comparable to the QCISD(T) data of Bieske et al . This contrasts with the later study of Massó and Wiesenfeld, where no such stationary point was found …”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations